The involvement of native speakers in teaching and learning Japanese language at UiTM / Choong Pow Yean, Sarinah Sharif and Normah Ahmad - Yean, Choong Pow; Sharif, Sarinah; Ahmad, Normah (Universiti Teknologi MARA, 2020)
The Nihongo Partner Program or "Japanese Language Partner" is a program that sends native speakers to support the teaching and learning of Japanese overseas. The program is fully sponsored by The Japan Foundation. The aim of this program is to create an environment that motivates the students to learn Japanese. This study is based on a survey of the Nihongo Partner Program conducted on students at UiTM, Shah Alam. This study aims to investigate whether there is a need for native speakers to be involved in teaching and learning of Japanese among foreign language learners and to what extent their engagement would help in teaching and learning process. Analysis of the results showed that students are in dire need of the Nihongo Partner Program to navigate the learning of the Japanese language through a variety of language learning activities. The involvement of native speaker increases students' confidence and motivation to converse in Japanese. The program also provides opportunities for students to increase their Japanese language proficiency and lexical density. In addition, with the opportunity to interact with the native speakers, students will have a better understanding of Japanese culture as they are able to observe and ask the native speakers. From the findings, it is irrefutable that involvement of native speakers is essential in teaching and learning of Japanese in UiTM.